Standardization of Dairy Products Through the Implementation of Pasteurization Technology and Aseptic Packaging - Rahmat Eka Putra; Ratni Prima Lita; Sri Melia; Indri Juliyarsi; Meuthia Meuthia; Devi Yulia Rahmi; Fatma Poni Mardiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
In order to enhance the quality of goat's milk products and ensure their cleanliness and safety for consumption, it is imperative to standardize the product and enhance its quality through the implementation of pasteurization technology and the utilization of aseptic packaging. Moreover, this initiative aims to enhance the sustainable commercialization of Rokir Farm's dairy products. Products can generate financial gains for companies while providing individuals with high-quality dairy products. Additionally, these items can support government initiatives to ensure food security and address nutritional deficiencies. This activity entails a collaborative effort between universities and partners to address particular challenges partners encounter in product standardization. Other goat milk-producing farmer groups can utilize this activity as a model.